A tool for simulating heat sharing opportunities between multiple buildings. Issue 4 (12th June 2017) - Botman, Roy; Schijndel, Jos van
Abstract : Purpose: The purpose of this paper is to present a tool for simulating heat sharing opportunities between multiple buildings. Design/methodology/approach: The approach is based on a building simulation model, HAMBase, in combination with an analytical programming code using MatLab. Findings: The tool provides a quick insight in possibilities for district heat sharing. It is able to operate without using too many parameters. From the results, it can be derived that storage tanks provide a great advantage in performance over the direct heat demand and supply method. Research limitations/implications: The main limitations are as follows: the used models are based on assumptions plus values derived from literature and a verification that is based on energy balance rules; and the MatLab code is verified by checking for possible errors, but is not completely validated. Originality/value: The main value of the work is that the presented methodology behind the tool is generally applicable and implementable in other models.